Students’ Perceptions on the Advantages of Learner-Centred Approaches and Grammar Teaching Methods in Selected Secondary Schools - Diyessa, Tamirat Tesfaye; Woldearegawie, Abebe Gebretsadik (Universitas Pendidikan Mandalika, 2025)
Nowadays, there is a shift from the traditional methods to the modern ones. Learner-centered methods have got due attention in language teaching because it encourages students to become active participants. However, in order to fully implement these methods, students’ perceptions on the advantages of learner-centered approaches and different grammar teaching methods play a great role. Accordingly, the purpose of this study was to investigate students’ perceptions on the advantages of learner-centered approaches and grammar teaching methods in secondary schools. The study utilized mixed methods research design, employing a questionnaire and an interview. The participants of the study were grade 9 students from three schools. Two hundred students for the questionnaire and six students for an interview were randomly selected. Questionnaire data was analyzed using mean and standard deviation. The interview data was analyzed thematically to support the questionnaire data. The findings of the study revealed students believe that using learner-centered approach in grammar lessons helps them to learn grammar effectively. Students had positive perceptions on some of the learner-centered-methods of grammar presentation. However, they had negative perceptions on some of them. As a result, they were more interested in grammar explanation by their teachers since they were accustomed by lecture method. Implications suggest that teachers are supposed to make students active participants by bringing various grammar tasks that arouse students’ interests; they should practice learner-centered methods namely pair work, group work, asking and answering questions and situational dialogue in order to build students’ confidence.